Biochemistry of Traditional Herbal Compounds and their Molecular Targets - Chinonso, Anih David; Kayode, Arowora Adebisi; Adondua, Moses Abah; Chinekwu, Ugwuoke Kenneth (Pharmacognosy Reviews)
Traditional herbal medicine represents a rich and diverse pharmacological reservoir that has long been utilized for treating various ailments across cultures. The growing interest in evidence-based phytotherapy has prompted rigorous scientific investigation into the biochemical and molecular underpinnings of many traditional herbal compounds. This review explores the biochemical nature, mechanisms of action, and molecular targets of five key phytochemicals: plumbagin, β-eudesmol, garcihombronane D, neferine, and iriflophenone 3-C-β-D-glucoside. A detailed analysis of their chemical structures, signaling pathways, and cellular effects is provided, contextualized with recent empirical findings. These compounds exhibit potent anti-inflammatory, anticancer, antioxidant, cardioprotective, and neuroprotective effects by modulating critical signaling pathways, including NF-κB, PI3K/Akt, MAPK, STAT3, and mTOR. Mechanistic insights reveal their roles in regulating apoptosis, autophagy, oxidative stress responses, and angiogenesis, with potential applications in treating chronic diseases. Integrating traditional knowledge with molecular biochemistry underscores the relevance of these natural products as promising candidates for modern drug development. Further preclinical and clinical investigations are needed to optimize their therapeutic application, pharmacokinetics, and bioavailability.
Keywords: Traditional Medicine; Phytochemicals; Molecular Targets; Herbal Compounds; Apoptosis; Natural Products